KEMAMPUAN MENULIS TEKS BERITA PADA SISWA KELAS IX SEMESTER GENAP SMP NEGERI 14 BANDAR LAMPUNG - Rachmasisca, Frieska Maryova (LPPM STKIP PGRI Bandar Lampung, 2016)
Motivating students to be able to write a text message properly, the necessary technical and stimulus to steer students toward teaching materials that will be applied. Then in order to achieve students' skills in writing news text educators should further enhance their creativity in teaching. While problems in the lift in this study that is how the level of students' skills in writing news texts ranging from mastering the contents of the topic, the use of diction, EYD, sentences are good and right and use the elements - elements of stories that cover the 5W + 1H. To achieve the research objectives and facilitate researchers to carry out research, the researchers applied quantitative descriptive method, this method is related to the way researchers to describe clearly and in detail with the percentage of students writing ability level text. While data collection techniques with techniques that assignment. The population in this research were 240 students and that the research sample was set at 40 students. Then the sampling technique used was proportional stratified random sampling. The results showed that students' skills in writing news text is 69.75%, the value being included in the criteria. While the value - average based on each indicator set is as follows: the average score based on indicators appropriateness of the contents to the topic is 66.87% it is included in the medium category, the average value is based on indicators of the completeness of the news that includes 5W + 1H which is 87.5% which is included in the excellent category, the average value is based on indicators of the use of diction reached 76.87%, it can be categorized in either criteria, the average value is based on indicators of good use of the phrase correctly ie 64.37%, this being included in the criteria, the average value is based on indicators of the use of the enhanced spelling is 55%, so included in the criteria for less.